Structural power distribution between family and non-family executives and innovation performance in family firms - Xiao Wei; Chen Ling (Journal of Innovation & Knowledge (JIK), 2023)
The top management team (TMT) of family firms is divided into two groups: family and non-family executives. Each group of executives is driven by different and multiple goals and motivations with distinct strategic innovation decision preferences. The centralized ownership and control of firms confer natural authority on family executives, and the appropriateness of the structural power distribution in the TMT has a significant impact on the level of participation and contribution of non-family executives to corporate innovation strategies that affects the innovation performance of family firms. Based on research of the power distribution of TMTs, this paper argues that a balanced structural power distribution (titles, compensation, representation) between family and non-family executives can improve the TMT interaction process, integrate information and knowledge of non-family executives, help balance economic and non-economic goals, and increase innovation performance. Moreover, we posit that this relationship becomes stronger with increasing board independence and environmental dynamism. We find support for these proposed relationships using a sample of publicly traded family firms in China representing 2,379 firm-year observations from 2009 to 2018. The implications of these findings extend to both family business and TMT research. and we offer practical guidance to encourage professional managers to actively participate in strategic decision-making and planned execution in family firms.
Keywords: 650; Innovation performance; Structural power distribution; TMT in family firms